Recuperação de zinco presente em efluentes industriais produzidos pela Votorantim Metais unidade Três Marias utilizando-se a técnica de extração líquido-líquido - Daniel Dayrell Pereira (2006)
The adequate treatment of industrial effluents and residues is imperative in order to avoid the contamination of environment. Such materials may pollute soil and rivers if discharged without treatment of even if they are conditioned in an inadequate way. In this context, the liquid-liquid extraction of zinc sulphate using D2EHPA as extractanthas been investigated in this work aiming for the recovery of zinc predominantly found in an industrial sulphuric acid effluent (pH around 3) produced by the Votorantim Metais, Unidade Três Marias, which contains other metallic species such as cadmium, cobalt, iron, lead, calcium, magnesium, manganese and nickel at several concentration levels. The study was carried out in two main steps, (1) extraction and stripping bench scale tests in order to assess adequate conditions for the favourable recovery of zinc from the effluent, and (2) continuous pilot scale tests using a mixer-settler battery aiming to reproduce the bench scale results. In the bench scales tests, the operating variables pH of the effluent (0.5 to 5.0), concentration of D2EHPA (5 to 50%w/w) and aqueous/organic volumetric phase ratio (1/5 to 5/1) were investigated in the extraction process while, in the stripping one, the organic/aqueous volumetric phase ratio (1/1 to 10/1) was studied by contacting a loaded organic phase with an industrial acid solution produced in the electrolysis. In the continuous mixer-settler study, it has been found that zinc can be selectively and quantitatively removed from the effluent in 3 extraction stages (pH = 2.5, [D2EHPA] = 20%w/w and A/O = 1) and other 3 stripping stages (O/A = 4). The overall recovery of zinc was 98.6% and a final solution containing 125.7 g/L of zinc that could be sent directly to electrowinning was obtained.